Dynamic mechanisms and targeted interventions in cerebral ischemia–reperfusion injury: pathological cascade from ischemia to reperfusion and promising therapeutic strategies - Meng, Xufeng; Zheng, Zhi; Yang, Li; Yang, Chen; Li, Xiaoli; Hao, Yunfei (Frontiers in Neuroscience, 2025)
Cerebral ischemia–reperfusion injury (CI/RI) is a critical event causing secondary neurological deterioration following vascular recanalization in patients with ischemic stroke (IS), involving multiple interrelated pathological processes that synergistically aggravate brain injury. However, the underlying mechanisms remain incompletely elucidated, necessitating systematic investigation. This review systematically elucidates the dynamic pathological mechanisms underlying CI/RI during ischemic and reperfusion phases. Hypoxia-induced mitochondrial energy failure and TLR4/NF-κB-mediated inflammation predominate in the ischemic phase, while reperfusion triggers a reactive oxygen species (ROS) burst, amplifying oxidative stress (OS). These interconnected cascades form a self-perpetuating pathological loop. Targeting these pathways, therapies such as the TLR4 antagonist ApTOLL, the iron chelator deferoxamine, and the free radical scavenger Edaravone have shown promise. Nevertheless, significant challenges persist, including single-target limitations, poor delivery efficiency across the blood–brain barrier, and insufficient mechanistic insights. By integrating dynamic mechanisms and corresponding therapeutic strategies, this review summarizes recent advances in understanding the core pathological mechanisms and targeted interventions for CI/RI, discusses the current status and future prospects of these mechanisms and therapies, and aims to provide a systematic framework for mechanistic insights into CI/RI and a theoretical foundation for its precision treatment.